Aberrant expression of Arpin in human breast cancer and its clinical significance. Issue 3 (9th December 2015) - Liu, Xiangping; Zhao, Bin; Wang, Haibo; Wang, Yu; Niu, Mengdi; Sun, Ming; Zhao, Yang; Yao, Ruyong; Qu, Zhiqiang
Abstract: Arpin (Arp2/3 complex inhibitor), a novel protein found in 2013, plays a pivotal role in cell motility and migration. However, the precise role of Arpin in cancer is unclear. This study investigated the expression of Arpin in breast cancer and evaluated its correlation with the characteristics of clinical pathology and prognosis of breast cancer patients. Immunohistochemistry (IHC) for Arpin protein was performed on formalin‐fixed, paraffin‐embedded 176 breast cancer tissues and 43 normal breast tissues while qRT‐PCR for Arpin mRNA with 104 paired tumour and paratumoural tissues from breast cancer patients respectively. The association of Arpin expression with clinical pathological features and survival was assessed in a retrospective cohort analysis of patients. The results showed that the expression of Arpin protein in cancer tissues was lower compared to that in normal breast and the expression of Arpin mRNA was also lower in cancer tissues than that in the matched paratumoural tissues. Among the 176 breast cancer patients, the lower expression of Arpin was significantly associated with advanced tumour, nodes and metastasis system stage, and the reduced Arpin expression was strongly associated with axillary lymph node metastasis using univariate and multivariate logistic regression analysis [odds ratio: 3.242; 95% confidence interval (CI): 1.526, 6.888; P < 0.05]. Furthermore, Arpin expression was an independent risk factor for recurrence‐free survival (HR: 0.373; 95% CI: 0.171, 0.813; P < 0.05). As Arpin expression was first examined in human breast cancer tissues with qRT‐PCR and IHC, our results suggest that Arpin downregulation may contribute to the initiation and development of breast cancer metastasis. Therefore, as a potential predictive marker, Arpin deserves future studies.